Implementasi Sistem Informasi Pelayanan Kantor Urusan Agama Kecamatan Babalan Berbasis Website - Syafina Raihanti; Ahmad Akbar; Nova Mayasari (CV. Hawari, 2025)
The advancement of information technology has driven many institutions to improve their services, including the Office of Religious Affairs (KUA). In this study, the author designed and developed a web-based information system aimed at supporting digital services at the KUA of Babalan District. This system is designed to facilitate three main services: family consultation registration, marriage dispensation letter requests, and applications for certificates of unmarried status. The system was developed using the Waterfall approach, which involves a series of stages from needs identification to testing and maintenance. Technically, the system utilizes PHP as the programming language, MySQL for database management, and Tailwind CSS to create a simple and user-friendly interface. Based on the testing results, the system has proven to be effective in accelerating service processes, reducing data entry errors, and making it easier for the public to access services online. Additionally, the system provides convenience for administrators, particularly in verifying documents. Overall, this system demonstrates significant potential in supporting the digitalization of services within the KUA environment.